Our immune system [videorecording] - Agaton, Michael; Bruce, Constance L.; Olsson, Mats Olof.; Sandell, Thore; National Geographic Society, Washington, D.C. (Washington, D.C. The Society in association with Sandell & Sons., 1988)
Gives a basic understanding of the immune system, how it protects the human body from disease-producing microorganisms. Explores the anatomy and physiology of both the immune system and its enemies - pathogenic microorganisms such as bacteria viruses and parasites. It also introduces AIDS as well as auto-immune diseases.
VHS.
Narrator, Monte Reid.
Keywords: Immune system; AIDS (Disease) -- Immunological aspects; Immunity